Dancing at "the People's Beach": Spontaneous Dialogue in the New York Sands - Pautz, Carolyn Renée (Journal of ecumenical studies, 2020)
Scholars of ecumenism and interreligious dialogue have largely ignored religions of African derivation in the Americas, such as Candomblé, Vodou, and Santería. This essay contributes to a resultant lacunae in the academic literature in these fields by using ethnography and performance theory (approaches that are also largely unknown in said fields) to illustrate the function of a spontaneous interreligious dialogue on a New York beach between Haitian Vodouists and Freemasons, one that effectively enhanced interfaith understanding on the popular level, as witnessed by a Lucumí priestess and scholar.